AKUNTABILITAS INFORMASI KEUANGAN ORGANISASI NIRLABA (PADA YAYASAN KESEJAHTERAAN PENDIDIKAN DAN PERUMAHAN (YKPP) DAN YAYASAN ABDI KARYA (YADIKA)) - Ulfa Sahara, - (2018)
The purpose of this research is to know the accountability of non-profit organization's financial information in the Yayasan Kesejahteraan Pendidikan dan Perumahan (YKPP) and Yayasan Abdi Karya (Yadika) located in DKI Jakarta. This research uses a qualitative approach etnometodologi, where research done to understand an activity based on process. The technique of analisis is done by triangulating the source of obtaining the same data from different sources. Informants in this research is the financial section directly involved in the preparation of financial statements and budget preparation. The findings obtained from research at YKPP and Yadika that in generating accountability of the foundation's financial information presented through some stage of them: First, the process planning. Second, approval process. Third, the process of the implementation of the activities. Fourth, the process of the preparation of the financial statement. Fifth, evaluation process financial position. Financial statement compiled by YKPP is statement of financial position, cash flow statement, the report changes assets net and notes to the financial statements that have been adapted the accounting standards PSAK No 45, but not full adapted because it must be adapted from the foundation. While Yadika prepare income statement and balance, not use PSAK No 45 in the preparation of the financial statement,because there is no policy set the standards preparation of the dinancial statement.